Elder Abuse in the LGBTQ2SA+ Community The Impact of Homophobia and Transphobia - Robson, Claire; Marchbank, Jen.; Gutman, Gloria; Prentice, Makaela (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book describes and analyzes the lived experience of elder abuse from the queer community. It discusses the experiences by transwomen, gay men and lesbians of financial abuse, physical and sexual abuse, homophobic abuse, and neglect within partner relationships, residential care, in home care, and religious organizations. Queer and trans elders have been described as 'The Silent Generation', since they have lived through times when their sexual and gender identities were criminalized and pathologized. The book shows that they are far more at risk to suffer abuse and neglect by those they should be able to trust, since they are more likely to have encountered all key risk factors, such as isolation, previous abuse and trauma, and mistrust of the health care system. Their vulnerability has been overlooked and this book addresses that gap. As such, this book provides a great resource to anyone working with elders, including medical professionals, care providers, police, counsellors, and policy makers.
1. Introduction -- 2. Methodology -- 3. Historical Context -- 4. Literature Review -- 5. Matthew's Story: Residential Care -- 6. Michele's Story: Residential Care -- 7. Trudy's Story: In home Care -- 8. Jackie's Story: In home Care -- 9. Joseph's Story: Partner Abuse -- 10. Pam's Story: Partner Abuse -- 11. Flygirl's Story: Abuse by Other Lesbians -- 12. Grace's Story: Spiritual Abuse -- 13. Candace's Story: Systemic Cultural Oppression -- 14. Interview with Courtney Dieckbrader: Seniors' Program Specialist at QMUNITY -- 15. Interview with Devan Cecelia Christian: Individual Counselor and Peer Group Facilitator for Indigo Survivors -- 16. Analysis and Discussion.
Keywords: Age distribution (Demography).; Sex; Quality of life; Gerontology; Aging Population; Gender Studies; Quality of Life Research; Gerontology